Using the Information Quantity Method to Assess the Regional Risk of Highway Slope to Improve the Level of Risk Management - Mingli Shao; Shuai Hou; Junfeng Gao (Advances in Civil Engineering)
In recent years, there have been many studies on regional geological hazard risk assessment. However, most previous research focused on natural geological disasters such as landslides and debris flows. There were few special regional risk studies aimed at highway slopes influenced deeply by artificial factors. According to the characteristics of highway slope, based on the evaluation of regional natural influencing factors, the artificial influencing factors and geological engineering information of an individual slope are introduced in this paper. The information evaluation model, combined with the analytic hierarchy process (AHP) and ArcGIS spatial analysis, was used to evaluate the risk of disaster in the study area. Then, the risk assessment results and risk zoning map along the highway were obtained. By comparing and analyzing the data of the management unit, the research results were in good agreement with the actual slope. The results of this paper can effectively guide the maintenance and management of highway slopes and provide a reference for site selection of subsequent highway reconstruction and expansion projects. In general, this study can improve the level of geological risk management in highway engineering.